Response of Mung Bean Varieties (Vigna radiata L.) to Application Rates and Methods of Blended NPS Fertilizer at Humbo - Fekadu Mekonen Mota; Dereje Shanka Balla; Mesfin Bibiso Doda (International Journal of Agronomy)
Mung bean is among the important dry-land legumes in the country and in the study area. However, the productivity of the crop is constrained by biotic and abiotic factors, mainly poor soil fertility, lack of adaptable varieties, and peer agronomic practices. Field trial was initiated at Humbo District with the objective of investigating the rate of NPS-blended fertilizer and application methods on overall performance of mung bean (Vigna radiata L.) varieties. The treatments comprised factorial combination of four rates of NPS (0, 50, 100, and 150 kg ha−1), two types of application methods (broadcasting and drilling), and two mung bean varieties (Shewa Robit and N-26) laid out in RCBD with three replications. Analysis of variance revealed that NPS rates and varieties significantly affected phenology and yield components. Application methods affected yield and thousand-seed weight. Two-way interaction of NPS rates with varieties significantly influenced plant height and pod plant−1. Three-way interactions also significantly influenced aboveground dry biomass and grain yield. The greatest dry biomass (4273.7 kg ha−1) and grain yield (1539.2 kg ha−1) were produced by N-26 variety with fertilizer composed of NPS at 150 kg ha−1 using the drill application method. Partial budget analysis also revealed that the highest (ETB 46,934.4 ha−1) net benefit was obtained at 100 kg NPS ha−1 with variety N-26 from the drilled method. Hence, growing N-26 with 100 kg NPS ha−1 applied using the drilling method of fertilizer application was found as the most suitable treatment combination to improve the income of farmers and increase productivity of mung bean.